2017
DOI: 10.1108/medar-09-2016-0080
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions, predictors and consequences of whistleblowing among accounting employees in Barbados

Abstract: Purpose Whistleblowing has been receiving increased attention and support in recent times as a means of detecting and correcting wrongdoing in organizations. This study aims to examine perceptions, attitudes and consequences (actions and reactions) of whistleblowing, as well as the predictors of internal and external whistleblowing intentions, by using Graham’s (1986) model of principled organizational dissent in a small emerging and collectivist culture like Barbados. Design/methodology/approach The study ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
65
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(81 citation statements)
references
References 37 publications
(104 reference statements)
6
65
0
2
Order By: Relevance
“…The variable of personal responsibility is empirically proven to positively affect the intention of civil servants to do whistleblow-ing. Result from this research is consistent with earlier researches by Curtis (2006), Robinson et al (2012) and Alleyne et al (2017). This indicates that personal responsibility is a factor that a person considers before blowing the whistle.…”
Section: Personal Responsibility Has a Positive Effect On The Intentisupporting
confidence: 91%
See 3 more Smart Citations
“…The variable of personal responsibility is empirically proven to positively affect the intention of civil servants to do whistleblow-ing. Result from this research is consistent with earlier researches by Curtis (2006), Robinson et al (2012) and Alleyne et al (2017). This indicates that personal responsibility is a factor that a person considers before blowing the whistle.…”
Section: Personal Responsibility Has a Positive Effect On The Intentisupporting
confidence: 91%
“…Ayers and Kaplan (2005) also Robinson et al (2012) discovered that personal responsibilities as being one of factors put into consideration before one becomes a whistleblower. Alleyne et al (2017) carried out a research in Barbados and found results showing that personal responsibility clearly does influence an accountants intention to do whistleblowing action. Thus making reach the first hypothesis as follows: H1: Personal responsibility positively influences the intention of civil servants to do whistleblowing action.…”
Section: The Effects Of Personal Responsibility On the Intention To Dmentioning
confidence: 99%
See 2 more Smart Citations
“…Alleyne (2017) believes that there are significant negative correlations between the whistle-blowing intention and the costs of whistle-blowing such as retaliation, threats, and damages, and that the auditor's perceived cost is higher. The lower the intention to whistle-blowing [19]. Dalton (2013) pointed out that Machiavellianism indirectly affects whistle-blowing intention through perceived costs and perceived benefits [20].…”
Section: Individual Factormentioning
confidence: 99%